Probabilistic, maximal covering location-allocation models for congested systems. - Marianov, Vladimir; Serra, Daniel (Journal of Regional Science, 1998)
Several probabilistic maximal covering location-allocation models with constrained waiting time for queue length are presented to consider service congestion in service networks such as health and emergency medical services and banking or distributed ticket-selling services. The first model takes into account the location of a certain number of single-server centers such that the maximum population is served within a standard distance, and nobody stands in line longer than a given time, or with more than a predetermined number of other users. Several maximal coverage models are consequently generated with one or more servers per service center. Finally, a new heuristic is developed to solve the models and is tested in a 30-node network.